(−)-Epigallocatechin-3-Gallate Inhibits Colorectal Cancer Stem Cells by Suppressing Wnt/β-Catenin Pathway - Chen, Yue (Nutrients, 2017)
The beneficial effects of tea consumption on cancer prevention have been generally reported, while (−)-Epigallocatechin-3-gallate (EGCG) is the major active component from green tea. Cancer stem cells (CSCs) play a crucial role in the process of cancer development. Targeting CSCs may be an effective way for cancer intervention. However, the effects of EGCG on colorectal CSCs and the underlying mechanisms remain unclear. Spheroid formation assay was used to enrich colorectal CSCs from colorectal cancer cell lines. Immunoblotting analysis and quantitative real-time polymerase chain reaction were used to measure the alterations of critical molecules expression. Immunofluorescence staining analysis was also used to determine the expression of CD133. We revealed that EGCG inhibited the spheroid formation capability of colorectal cancer cells as well as the expression of colorectal CSC markers, along with suppression of cell proliferation and induction of apoptosis. Moreover, we illustrated that EGCG downregulated the activation of Wnt/β-catenin pathway, while upregulation of Wnt/β-catenin diminished the inhibitory effects of EGCG on colorectal CSCs. Taken together, this study suggested that EGCG could be an effective natural compound targeting colorectal CSCs through suppression of Wnt/β-catenin pathway, and thus may be a promising agent for colorectal cancer intervention.